2019
DOI: 10.1111/jnc.14863
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of unique C‐terminal sites of the mu‐opioid receptor variants 1B2 and 1C1 influences their Gs association following chronic morphine

Abstract: We recently demonstrated in rat spinal cord that a regimen of escalating doses of systemic morphine, analogous to regimens used clinically for chronic pain management, selectively up‐regulates the mu‐opioid receptor (MOR) splice variants MOR‐1B2 and MOR‐1C1 mRNA and functional protein. This study investigated the potential relevance of up‐regulating MOR‐1B2 and MOR‐1C1 to the ability of chronic morphine to shift MOR signaling from predominantly Gi/Go inhibitory to Gs stimulatory. Specifically, we tested the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 89 publications
(149 reference statements)
0
4
0
Order By: Relevance
“…Within-system drug tolerance occurs when opposite reactions are elicited within the same system. A recent study has indicated that chronic morphine use induced a shift in MOR signalling from the predominantly inhibitory Gi/Go adenylyl cyclase to the stimulatory Gs adenylyl cyclase through the upregulation of different MOR receptor variants ( 68 ). Specifically, chronic morphine use induced the phosphorylation of the carboxyl terminal sites on MOR-1B2 and MOR-1C1, enhancing Gs protein association ( 68 ).…”
Section: Proinflammatory Cytokines In Morphine Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Within-system drug tolerance occurs when opposite reactions are elicited within the same system. A recent study has indicated that chronic morphine use induced a shift in MOR signalling from the predominantly inhibitory Gi/Go adenylyl cyclase to the stimulatory Gs adenylyl cyclase through the upregulation of different MOR receptor variants ( 68 ). Specifically, chronic morphine use induced the phosphorylation of the carboxyl terminal sites on MOR-1B2 and MOR-1C1, enhancing Gs protein association ( 68 ).…”
Section: Proinflammatory Cytokines In Morphine Tolerancementioning
confidence: 99%
“…A recent study has indicated that chronic morphine use induced a shift in MOR signalling from the predominantly inhibitory Gi/Go adenylyl cyclase to the stimulatory Gs adenylyl cyclase through the upregulation of different MOR receptor variants ( 68 ). Specifically, chronic morphine use induced the phosphorylation of the carboxyl terminal sites on MOR-1B2 and MOR-1C1, enhancing Gs protein association ( 68 ). In between-system adaptation, different drug-sensitive systems are linked to the drugs' primary action system.…”
Section: Proinflammatory Cytokines In Morphine Tolerancementioning
confidence: 99%
“…Recent research has shown that chronic morphine use leads to an increase in the expression of a subset of the MOR receptors that signal via the stimulatory Gs adenylyl cyclase rather than the predominantly inhibitory Gi/Go adenylyl cyclase. In particular, MOR-1B2 and MOR-1C1 had their carboxyl-terminal regions phosphorylated due to chronic morphine usage, which increased their interaction with Gs proteins (10) .…”
Section: Proinflammatory Cytokines In Morphine Tolerancementioning
confidence: 99%
“…There are also factors unrelated to HIV that can worsen neuroHIV pathology. One such comorbid insult is opioid use disorder (OUD) (Fitting et al, 2010(Fitting et al, , 2020Hauser et al, 2006;Murphy et al, 2019), which can by itself dysregulate TDP-43 kinase (Chakrabarti et al, 2020;Wager et al, 2014). Hence, we also evaluated the impact of morphine, a prototypical opioid of abuse/misuse, in some outcome measures.…”
Section: Introductionmentioning
confidence: 99%